VictoriaSecret.bygagak / Aqilah Salleh - Salleh, Aqilah (2021)
The Social Media Portfolio is one of the assignments that has been entrusted to all HM2404B students under the subject Principles of Entrepreneurship (ENT530). In the assignment, all students are required to create a Facebook account to set up their own business that will be operated online. There are several steps that have been given by Dr. Zawani bin Mamat@Ibrahim as a guide for all students to start a business and end by making a report on the business that has been done. The business I have set up on the Facebook page is selling Victoria Secret brand perfume called VictoriaSecret.bygagak. In order to complete this social media portfolio assignment, students need to provide a registration form in Go-ecommerce that has been filled in as proof of business registration. In addition, in this assignment also need to introduce the business VictoriaSecret.bygagak such as name, address, organizational chart that has been established in the business VictoriaSecret.bygagak, mission and vision, describe more information about the product marketed that is Victoria Secret perfume and list all sales product prices. In addition, creating an account and providing a Facebook page URL link is also stated to facilitate the search for VictoriaSecret.bygagak business on social media sites. A teaser video is also provided as an introduction to VictoriaSecret.bygagak branded business startups and products. Last but not least, the task also requires activities in hard sell and soft sell techniques that have been done by VictoriaSecret.bygagak on the social media site Facebook.